Validity of PBL-Based E-Modules to Improve Students' Critical Thinking Skills on Global Warming in Grade X of SMA Negeri 9 Padang - Philothra, Evan (PILLAR OF PHYSICS EDUCATION, 2025)
The rapid progress of science and technology (IPTEK) in the twenty-first century, which has profound effects on many facets of life, including education, served as the impetus for this study. In the field of education, technology is crucial to maintaining the flow of educational activities. The use of electronic-based teaching resources, such e-modules, is one way that technology is applied in the educational process. The objective of this study is to develop an e-module based on Problem-Based Learning (PBL) to enhance the critical thinking skills of Grade X students at SMA Negeri 9 Padang on the topic of global warming. The e-module In addition to being sound in terms of content and structure, it is expected to provide students with a more meaningful and engaging learning experience.The development model used in this inquiry was based on Plomp's (2013) model. The validation process was conducted by three physics professors from the University of Padang (UNP). Taking into account the results of the validation instrument analysis, the developed e-module obtained a validation score of 0.93, which falls into the valid category. Therefore, this PBL-based e-module is deemed valid and suitable for use as an innovative teaching material to support the enhancement of students' critical thinking skills in understanding the topic of global warming.